Lightbulbs and nappies: sustainable development and customer perceptions. (7th February 2008) - Short, Tim; Harvey, Joan
Recent interest in 'green' versions of everyday objects has led to a market presence for energy-efficient lightbulbs and the re-emergence of reusable nappies (diapers). Given their ease of use, one might think that 'green' lightbulbs would become far more popular than reusable nappies and the associated inconvenience. However, this is not always the case. The paper takes a novel approach to understanding consumers' behaviour, using functional analysis to examine 'green' and 'normal' products and demonstrating why some refuse to use energy-efficient lightbulbs, despite using reusable nappies. It considers how consumer perceptions have developed and the implications for engineering designers.